8-2x=3x+43

Simple and best practice solution for 8-2x=3x+43 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8-2x=3x+43 equation:


Simplifying
8 + -2x = 3x + 43

Reorder the terms:
8 + -2x = 43 + 3x

Solving
8 + -2x = 43 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
8 + -2x + -3x = 43 + 3x + -3x

Combine like terms: -2x + -3x = -5x
8 + -5x = 43 + 3x + -3x

Combine like terms: 3x + -3x = 0
8 + -5x = 43 + 0
8 + -5x = 43

Add '-8' to each side of the equation.
8 + -8 + -5x = 43 + -8

Combine like terms: 8 + -8 = 0
0 + -5x = 43 + -8
-5x = 43 + -8

Combine like terms: 43 + -8 = 35
-5x = 35

Divide each side by '-5'.
x = -7

Simplifying
x = -7

See similar equations:

| 6x-32=0 | | 7x+9=-79 | | br-1+6r=11 | | 5(k+3)=2(k+7)-5 | | 2-3a+7=8a+3-a | | 16x(2x-9)=4(8x+8) | | 4x+6=74 | | 16y=180 | | 2m+7=2m-9 | | 6x+58=0 | | 2(x-3)=-24 | | 3(y-2)=y+8 | | 10x-3=6x+39 | | a=-5n+2n | | 2x+1=53 | | 5x+64=180 | | 7(11x-8)=77x-10 | | 13.0x-180forx=50 | | 8g+6=9g-10 | | x+77+x+62+45=180 | | 2(3x-7)=(5x-6) | | 9(x+5)=108 | | (2x+43)=(2x-3) | | X+-16=9 | | 13x-1=8x+39 | | n^2=-n | | 3*2-5+4*3-8+5*2= | | x-4+1=-3-x | | 3+3u=18 | | 250+150x=300y | | 10-3p+4p=20 | | F(4)=-3(-9)+10 |

Equations solver categories